Periodic therapeutic plasma exchange in patients with moderate to severe chronic myasthenia gravis non-responsive to immunosuppressive agents: An eight year follow-Up - Triantafyllou, N.I.; Grapsa, E.I.; Kararizou, E.; Psimenou, E.; Lagguranis, A.; Dimopoulos, A. (Therapeutic Apheresis and Dialysis, 2009)
Few patients with moderate or severe myasthenia gravis (MG) do not respond to immunosuppressive treatment. We present our experience with periodic therapeutic plasma exchange (TPE), in 11 patients with MG resistant to intravenous immunoglobulin (IVIg) therapy, who had frequent relapses even whilst on high doses of immunosuppressive drugs, over a period of 8 years. All patients underwent TPE until control of their symptoms was achieved, and afterwards TPE sessions were continued periodically in an attempt to achieve remission of the disease, without immunosuppressant therapy. Two of the patients were progressively weaned off immunosuppressive agents, as well as TPE, and they are now symptom free. The other nine patients are still under a periodic TPE regime. Seven of them were weaned off all medications and required an average of 3.7 TPE sessions per year during the last 5 years. In the other two patients, those with the most severe form of the disease, the immunosuppressant dosage has been decreased and a TPE session every 2-3 weeks is required in order to control their symptoms. Through all these years TPE has been well tolerated and only minor side-effects were observed in two patients. Finally, during this 8 year follow-up period, nine of the patients treated with periodic TPE have been in good control of their symptoms over the last 5 years, and the other two patients live a normal life without any treatment in the last 3 years. Our results suggest that periodic TPE is safe and effective in the control of symptoms in patients with moderate to severe MG who do not respond to immunosuppressive therapies. © 2009 International Society for Apheresis.
Keywords: Immunosuppressive therapy; Intravenous immunoglobulin; Myasthenia gravis; Periodic plasma exchange; Plasmapheresis; Therapeutic plasma exchange